Higher Educational Attainment Associated with Optimal Antenatal Care Visits among Childbearing Women in Zambia - Muyunda, Brian; Makasa, Mpundu; Jacobs, Choolwe; Musonda, Patrick; Michelo, Charles (Frontiers in Public Health, 2016)
ABSTRACT Objective Attendance of at least four antenatal care (ANC) visits over the period of pregnancy has been accepted by World Health Organization (WHO) to comprise the optimal and adequate standard of ANC because of its positive association with good maternal and neonatal outcomes during perinatal period. Despite the free ANC being provided, many pregnant women have been found not to meet this minimum number of ANC visits in Zambia. We investigated if educational attainment is associated with optimal ANC visits among childbearing women in Zambia. Methods Data stem from the 2007 Zambia Demographic and Health Survey (ZDHS) for women aged 15-49 years who reported ever having been pregnant in the five years preceding the survey. The linked data comprised socio-demographic and other obstetrical data which were cleaned, recoded and analyzed using STATA version 12 (Stata corporation College Station, Texas). Multivariate logistic regression was used to examine the association of educational attainment and other background variables. Results Women who had higher education level were more likely to attend at least four ANC visits compared to those with no education [AOR 2.8, 95% CI 1.51-5.15; p=0.001]; this was especially true in the urban setup. In addition, women with partners with higher education level were also more likely to have optimal ANC attendance [OR 2.0, 95% CI 1.3- 3.1, p=0.002]. Conclusion There were marked educational attainment associated differentials linked with meeting the required ANC attendance in this population, suggesting access to health care inequity-related dynamics and imbalances in uneducated groups.